Las obligaciones tributarias y su nvel de cumplimiento en la empresa unidad educativa América, cantón Quevedo, Período 2013. - Guerrero Zambrano, Gabriel Marcelo (2015)
The research work consisted of the application of the tax audit to America educational unit during the period of January 1 to December 31, 2013, in order to analyze the fulfillment of tax obligations according to the provisions of the law on tax procedure, its implementing regulation, tax code, as well as the accounting principles generally accepted for establishing a reconciliation between the aspects of legal and accounting to determine the tax base and taxes that affect the audited taxpayer.. Set as main objective to determine tax obligations and the level of compliance in the company to verify that the information submitted to the tax administration, appropriate operations recorded in the accounting books and the supporting documentation; as well as to all the economic transactions in order to detect temporary and/or permanent differences and establish tax objections, in accordance with the accounting and tax regulations. Methodologically techniques and tools were used tributaries that they allowed performing the audit to ensure that taxes are properly applied and supported using the information provided by those responsible for the accounting and……………..